Building a data-driven website with Adobe Dreamweaver CS5.5 : learn by video - Mairs, Candyce (Peachpit Press : Video2brain, 2011)
"This innovative product is a focused video workshop and accompanying 48-page full-color book that teaches web developers how to use Adobe Dreamweaver CS5.5 to code websites that use databases to update pages with changing information. The video begins with a description of the database-driven website process, including installation of the development environment. Then it explains how to pull data from a database and display it in a variety of ways using Dreamweaver features; and how to pass data between pages. The video also covers building an administration interface to insert and update database data using web forms. Experienced instructor, Candyce Mairs presents three hours of exceptional quality video tutorials, complete with lesson files, assessment quizzes, and review materials. The video is wrapped in a unique interface that allows the viewer to jump to any topic and also bookmark individual sections for later review. The unique Watch-and-Work mode shrinks the video into a small window to allow the student to work alongside in Dreamweaver. Project files used in the lessons are included on the disc so viewers can practice what they've learned, and interactive review questions help reinforce freshly gained knowledge."--Resource description page.